THE SOVIET REGIME AND TRANSFORMATION OF CULTURAL NOMENCLATURA IN SOVIET-LITHUANIA AFTER THE 70’S: THE CASE OF WRITERS - Ivanauskas, Vilius (Politologija, 2015)
The purpose of the cultural elite members during soviet period was designated for the implementation of soviet indoctrination and legitimization of the regime. This task provided for those cultural elites not only the authority, symbolic capital and prestige among other societal groups, but also the strict mechanisms of control, censorship and public behavior. Even this model was valid for soviet Lithuania, the analysis of their relationship with the system in the late socialism reveals that local intellectuals and other cultural elite’s members who were part of soviet cultural establishment transferred to the multi-edge relationship with the system. This article is an attempt to apply socio-political perspective analyzing soviet system. By observing the erosion of the system, the rise of ethnic and local interests and the digress of everyday life from official goals it is importantly to argue that during the period of late socialism local elites of cultural establishments diminished their participation in soviet indoctrination processes and made significant influences mobilizing the national identity. After the Brezhnev gained the power and especially after Prague Spring in 1968, there was a collective disappointment among many intellectuals regarding soviet values. When Brezhnev doctrine was introduced it was clear that ideology cannot be inter preted anymore and the status quo and dogmatism was the most preferable position for the political elite. In this context, the mainstream of local cultural elite responded to the decline of values and has changed their engagement to the soviet system, expanding their focus to ethnic traditions, local history and symbols and sharing their attitudes in informal networks, who often served for intellectuals as analogues of public spheres (concept of V. Klumbys, 2009). This perspective pays attention to the conditions of late socialism, when communist ideology was turned to dogmatic position and everyday life alongside with ideological rituals also reflected informal practices helping to solve shortages, avoiding strict control and gently bringing new ideas. By taking the case of soviet writers, several intellectuals circles could be identified and this deployment could be sustained as a reflection of the rest of cultural elite. These groups not maintained constructed different relationship with the system or national ideology, but also experienced the intensive struggle for the power in local cultural establishments. The group of ideologists gradually lost their influence to the group of conservatist, who in the 70–80 occupied main chairs in cultural institutions and who were more enthusiastic towards ethnic issues, but being a part of cultural nomenclatura they also found consensus with local party apparatchiks. Another part of cultural nomenclatura – ideologists could not also gained the public recognition as conservatists or the famous intellectuals from local intelligentsia circles (moderate writers), who have increased their authority for their talent and deep attachment to local and ethnic issues. Emphasizing the orientation to localism among conservatists and their close relations with the circles of moderate intellectuals under the conditions of late socialism, this article argues that significant part of cultural nomenclatura digressed from soviet indoctrination practices converting to the support of national ideology and accumulating the cultural capital, which has played important role in national revival in 90’s.